Hypoxia inducible factors regulate pneumovirus replication by enhancing innate immune sensing - Jiyeon Ha; Parul Sharma; Sammi Ta; Senko Tsukuda; James M. Harris; Rebekah Penrice-Randal; Eleanor Bentley; Adam Kirby; Daniele F. Mega; David A. Matthews; Peter Balfe; Jan Rehwinkel; et al. (Proceedings of the National Academy of Sciences, 2026)
The immune mechanisms responsible for protection and pathogenesis in pneumoviral infection are not well defined. We demonstrated that pharmacological activation of the hypoxic inducible factor (HIF) signaling axis using daprodustat limited viral replication through enhanced immune signaling. Transcriptomic analysis revealed HIF augmented activation of innate immune response genes, including interferon-stimulated gene 15 ( Isg15 ), in the lung and spleen of mice infected with pneumonia virus of mice (PVM). In human respiratory syncytial virus (hRSV)-infected airway epithelial cells, daprodustat inhibited viral replication and enhanced ISG15 expression in a HIF-dependent manner. Importantly, inhibition of type I interferon signaling or the RIG-I sensing pathway abrogated the antiviral activity of HIF. Moreover, daprodustat increased interferon signaling in response to viral RNA, suggesting that HIF inhibits pneumovirus replication through enhancing viral RNA sensing. Mechanistically, daprodustat reduced N 6 -methyladenosine modification of viral RNA through upregulation of RNA demethylases, promoting detection by innate immune sensors. This study highlights the intricate interplay between hypoxia and antiviral immunity and offers valuable insights into pneumovirus–host interactions and potential therapeutic interventions.